Application of Covariance Matrix Adaptation-Evolutionary Strategy for Modified Constrained Optimal Power Flow Problem Incorporating Valve Point and Emission Effect - Hari Krishna Achuthan Parthasarathy; Madhusudan Saranathan; Tamilselvi S.; Karuppiah N.; Praveen Kumar Balachandran; Dhanamjayulu C.; Baseem Khan; Thamilmaran A. (International Transactions on Electrical Energy Systems)
A prevailing problem in power and energy subsystems is the smooth operation of electric energy systems. This work presents recent, efficient, and reliable evolutionary algorithm for solving the optimal power flow (OPF) analysis. All various practical complex equality and inequality constraints, namely, bus voltages, real powers of the generator buses, tap settings of the transformers and the reactive power generations, shunt compensation, and emission, are considered for the real-world scenario. Primary feature in a gas power plant that raises a lot of computational shortcomings with nonlinear structure in fuel cost is valve point effect. The existing research works have not factored the valve point effect and lack the accuracy in the fuel cost minimization and do not reflect the various practical complexities such as valve point and emission effects in the OPF problem formulation. This paper, for the first time, introduces modified OPF problem formulation incorporating valve point effect and applies covariance matrix adaptation-evolution strategy (CMA-ES) for solving the modified OPF problem. The algorithm is scrutinised and tested on a modified IEEE-30-bus platform for various OPF objectives such as cost minimization, transmission loss, and total voltage deviation, subjected to practical constraints. Load flow analysis has been carried out using the Newton–Raphson method. This work aims to lay the foundation in such a way that it can be applicable in a real-world scenario for any number of buses.